Strategi ketidaksantunan sarkasme warganet pada kolom komentar Instagram Ganjar Pranowo - Risya Ayu Irawati; Eva Tuckyta Sari Sujatna; Susi Yuliawati (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2023)
This study is motivated by the increasing use of social media among people who do not fully understand the rules of interacting and communicating. This study aims to (1) reveal the strategy of impoliteness of sarcasm displayed and (2) reveal the markers of impoliteness that show sarcasm of netizens in the comments column on Ganjar Pranowo's Instagram account. Data were obtained from 7 posts on Ganjar Pranowo's Instagram account from March 28 to April 4, 2023. This research is descriptive qualitative research using the methods of listening, noting, and recording with a pragmatic approach. The results showed that netizens used irony in writing sarcasm disrespect strategy comments. In addition, four markers of sarcasm impoliteness strategy are in the comment column on Ganjar Pranowo's Instagram. These markers include the use of profanity-related diction by 35%, the use of ALL CAPS by 25%, excessive use of exclamation marks by 20%, and inappropriate name-calling used by 20%. There were no markers found related to taboo language, such as animal names or body parts. Some data also showed the use of figurative language to indicate sarcasm. Netizens' impoliteness is often triggered by several issues concerning football, politics, and religion.